Learners’ Perceptions of Social Media-Based Vocabulary Learning: Insights from TikTok, Instagram, and YouTube Users in an EFL Context - Baureh, Gabriella Alleid Dian; Neman, Meily Ivane Esther (Journal of English Language and Education, 2025)
This study examines learners’ perceptions of utilizing social media platforms, including TikTok, Instagram, and YouTube, as tools for acquiring English vocabulary. Recognizing that vocabulary is a key component of communicative competence, this research examines how informal, multimodal exposure through social media supports incidental vocabulary learning. A qualitative descriptive design was employed involving eight EFL students from a private university in Manado, Indonesia, who actively use social media for English learning. Data were collected through semi-structured interviews and analyzed thematically to identify patterns in learners’ experiences, strategies, and challenges. Findings reveal that most learners prefer video-based content for its visual clarity, contextual richness, and entertainment value, which foster motivation and engagement. Learners employed a combination of strategies, including note-taking, translation, and pronunciation practice, to enhance word retention. Participants viewed social media as an effective and enjoyable platform for vocabulary acquisition; however, they also encountered difficulties with accent comprehension, word retention, and technical constraints. The study finds that social media is a good supplement to formal education because it helps students learn on their own and exposes them to real language. It recommends that teachers integrate social media-based activities into classroom tasks to support vocabulary enrichment. Future research could employ mixed-method or experimental designs to measure the actual impact of social media exposure on vocabulary development.